The Effectiveness of Ultraviolet, Ozonization and Reverse Osmosis as Disinfection Method in Drinking Water Refill Stations - Sri Yusnita Irda Sari; Muhamad Iqbal; Adi Imam Cahyadi; Titik Respati; Ardini Saptaningsih Raksanagara; Ridad Agoes (Universitas Islam Bandung, 2018)
The number of drinking water refill stations (DWRS) was increased rapidly because high of mid-low urban community need to get affordable drinking water. Water treatment methods in DWRS are varying even many DWRS uses more than one disinfection method to increase the effectiveness. The quality of many DWRS productions was reported unstandardized, however not yet the study to evaluate the effects of the water treatment method used. This study aimed to compare the effectiveness of various water treatment methods in DWRS to identify which method is the most effective. The study used a cross-sectional approach conducted in 3 groups of water treatment methods, namely ultraviolet, ultraviolet + ozonization, and a combination of ultraviolet + ozonization + reverse osmosis with each group consisted of 40 DWRS. The survey was conducted in July–September 2017 in Bandung municipality by structured interview. Examination of microbiological parameters of raw and processed drinking water samples using membrane filter method. Water samples from raw water and drinking water from treatment process were taken from each DWRS to be tested for the microbiological parameter by using the membrane filter method. Comparison of the effectiveness was analyzed using the Wilcoxon rank sum test and assessment of log removal reduction. The result showed that there was significantly different in the effectiveness of coliform removal between the three groups. The improvement for controlling and training particularly for the procedure and maintenance of water treatment equipment to the owners/workers in DWRS is urgently needed as the concern of related authority. In conclusion, the water treatment method using reverse osmosis and ultraviolet is the most effective disinfection method compared to the ozonization method. The usage of more that one method of water treatment at the same time relate to the lower percentage of the effectiveness compares to the usage of only one method. EFEKTIVITAS ULTRAVIOLET, OZONISASI, DAN REVERSE OSMOSIS SEBAGAI METODE DESINFEKSI DEPOT AIR MINUM ISI ULANGPerkembangan depot air minum isi ulang (DAM) melaju dengan pesat karena masyarakat menengah ke bawah perkotaan membutuhkan air minum dengan harga yang terjangkau. Metode pengolahan air baku menjadi air minum di DAM bervariasi bahkan tidak jarang digunakan lebih dari satu metode desinfeksi untuk meningkatkan efektivitasnya. Kualitas produksi DAM banyak yang dilaporkan tidak sesuai dengan standar, namun belum terdapat penelitian yang mengevaluasi pengaruh metode pengolahan air yang digunakan. Penelitian ini bertujuan membandingkan efektivitas berbagai metode pengolahan air di DAM sehingga dapat diketahui metode apa yang paling efektif. Penelitian ini menggunakan pendekatan cross-sectional yang dilakukan pada 3 kelompok metode pengolahan air, yaitu ultraviolet, ultraviolet + ozonisasi, dan kombinasi ultraviolet + ozonisasi + reverse osmosis dengan tiap-tiap kelompok terdiri atas 40 DAM. Survei dilakukan pada Juli–September 2017 di Kota Bandung dengan melakukan wawancara terstruktur. Sampel air baku dan air minum hasil olahan diambil dari setiap DAM untuk diperiksa parameter mikrobiologinya menggunakan metode filter membran. Perbandingan efektivitas dianalisis menggunakan Wilcoxon rank sum test dan penilaian log removal reduction. Hasil penelitian menunjukkan bahwa terdapat perbedaan efektivitas yang signifikan pada ketiga kelompok terutama efektivitas terhadap coliform. Perlu upaya pengawasan dan pelatihan khususnya mengenai teknis pemakaian dan pemeliharaan alat pada pemilik/pekerja DAM yang harus menjadi perhatian pemerintah dan pihak terkait. Simpulan, metode pengolahan air menggunakan reverse osmosis dan ultraviolet merupakan metode desinfeksi yang paling efektif dibanding dengan metode ozonisasi. Pemakaian lebih dari satu metode desinfeksi pada saat yang bersamaan menyebabkan persentase efektivitas menjadi lebih rendah dibanding dengan yang menggunakan hanya satu jenis metode desinfeksi.